Los juegos populares como estrategia didáctica para desarrollar el aprendizaje de las ciencias naturales del sexto año de educación general básica paralelo “a” de la Unidad Educativa "Ángel Polibio Cháves" de la ciudad de Guaranda, provincia bolívar en el periodo lectivo 2022 - 2023. - Naranjo Aguirre, Kerly Brigith (2023)
This research report for titling purposes sIt was carried out in order to link popular games with the scientific knowledge of natural sciences and improve the development of learning of said subject. For this process, games were identified in relation to the themes of each unit and in this way adapt them in the educational field. The collection of information that theoretically supports the study was also carried out, the data collection technique is the analysis of texts such as the natural sciences book and the student's homework notebook and after that a test to verify the viability of the study. job offers. It is determined that popular games are not only a means of entertainment